(untitled) (Web of Teachers: Inderscience Research, 2026)
Today, the development of the preschool education system is one of the priorities of state policy. Because it is during the preschool years that a child’s intellectual potential, worldview, spiritual values, and social skills are formed. In this regard, the Presidential Decree No. PF-19 of the Republic of Uzbekistan dated February 5, 2026 is an important document aimed at radically modernizing the preschool education system, introducing international experience, and creating a quality educational environment.